Narrating the Political Hero: The Construction of the Fictional Political Leader in the Obama Era - Hernández-Santaolalla, Victor; Sola-Marales, Salome (Academic Quarter | Akademisk kvarter, 2013)
Like a distorted mirror, mass culture products generally give back an exaggerated reflection of the sociocultural context. In this regard, from a historical perspective, 9/11 attacks launch a warning to global society that no individual or nation was completely safe. This has created a climate of fear that would be intensified with the Iraq war and the global economic crisis. This atmosphere will translate to audiovisual fiction as stories where anyone can be the enemy, even political leaders. So the boundaries between heroes and villains are uncertain. With the 2008 Presidential Elections, the United States started a new era whose predominant narrative would be to accept and overcome past mistakes, in order to be the great nation it once was. In sum, we aim to expose how fictional construction of political leaders has evolved since Obama’s victory, illustrating this with examples from films and TV shows.